Peranan Camat Dalam Meningkatkan Kinerja Aparatur Sipil Negara di Kecamatan Hinai Kabupaten Langkat - bahrum, bahrum; Adam , Adam; Sembiring, Walid Musthafa (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political UMA), 2025)
This study will analyze the sub-district head's role in improving the State Civil Apparatus (ASN) performance in Hinai District, Lalat Regency, and identify the inhibiting factors. Using a descriptive qualitative approach through observation, interviews, and documentation. The respondents interviewed included the Sub-district Head, the Sub-district Secretary, the head of the section, and the local community to get a comprehensive picture of the role of the Sub-district Head in improving the performance of ASN. This research shows that sub-districts have a strategic role as policymakers, leaders, motivators, supervisors, and ASN coaches. The sub-district head also encourages the improvement of ASN competencies through training, optimization of the use of technology, and strengthening accountability and transparency of public services. However, the effectiveness of the role of the sub-district head faces internal obstacles, such as low technological competence of ASN, resistance to change, and limited human resources. External barriers include limited technological infrastructure, minimal budgets, and increasing societal demands. To overcome this challenge, the sub-district needs to develop strategies such as continuous training, socialization of the importance of innovation, optimization of task division, and cooperation with local governments and external parties to improve the performance of civil servants and the quality of public services.